Rain man - Metro Goldwyn Mayer; The Guber-Peters Company; Argentina Video; Star Partners II Ltd.; Mirage Entertainment ([Los Angeles, Calif.] United Artists, 1998)
"My father has stuck it to me all my life", complains Charlie Bobbit (Tom Cruise), a callous self centered young hustler who feels he's been cheated out of his 3 million dollar inheritance. Left only with his late father's prized rose bushes and a vintage 49 Buick convertible, Charlie soon uncovers yet another surprise--a brother he never knew he had. Dustin Hoffman's Oscar winning portrayal of Raymond, an autistic savant living in a world devoid of normal perceptions, may well be the crowning achievement of his distinguished career. Discovering Raymond in an institution, Charlie abducts him in a last ditch to extort his "fair share" of the family estate. What begins as an unsentimental journey across the country, evolves into a mystical odyssey of love and self revelation as Raymond forces. Charlie to grow beyond the limits of his own handicapped heart.
Summary from the cover.
VHS.
Title from container.
Writer: Barry Morrow ( story); Ronald Bass (screenplay)
Casts: Dustin Hoffman; Tom Cruise; Valeria Golino; Gerald R. Molen; Jack Murdock ...[et.al.]
Gift
English; Italian; color (technicolor); Dolby digital.
Keywords: Inheritance -- Father-son estrangement -- Drama; Bankruptcy -- Casino -- Violence; Autistic savant -- Autism -- Psychiatry; Cincinnati, Ohio, USA; Las Vegas, Nevada, USA; Biographical films; Feature films